Postoperative complications in cirrhotic pediatric deceased donor liver transplantation: Focus on transfusion therapy. (5th July 2017) - Nacoti, M.; Cazzaniga, S.; Colombo, G.; Corbella, D.; Fazzi, F.; Fochi, O.; Gattoni, C.; Zambelli, M.; Colledan, M.; Bonanomi, E.
Abstract: Intraoperative transfusions seem associated with patient death and graft failure after PLTx. A retrospective analysis of recipients' and donors' characteristics and transplantation data in a cohort of patients undergoing PLTx from 2002 to 2013 at the Bergamo General Hospital was performed. A two‐stage hierarchical Cox proportional hazard regression with forward stepwise selection was used to identify the main risk factors for major complications. In addition, propensity score analysis was used to adjust risk estimates for possible selection biases in the use of blood products. Over the 12‐year period, 232 pediatric cirrhotic patients underwent PLTx. One‐year patient and graft survival rates were 92.3% and 83.7%, respectively. The Kaplan‐Meier shows that the main decrease in both graft and patient survival occurs during the first months post‐transplantation. At the same time, it appears that most of the complications occur during the first month post‐transplantation. One‐month and 1‐year patient complication‐free survival rates were 24.8% and 12.1%, respectively. Our study shows that intraoperative red blood cells and platelet transfusions are independent risk factors for developing one or more major complications in the first year after PLTx. Decreasing major complications will improve the health status and overall long‐term patient survival after pediatric PLTx.